2022
DOI: 10.1007/s00210-022-02267-7
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effects of a lipid transfer protein isolated from Morinda citrifolia L. (noni) seeds on irinotecan-induced intestinal mucositis in mice

Abstract: This work aimed to evaluate the activity of a lipid transfer protein isolated from Morinda citrifolia L. seeds, McLTP 1 , on the development of intestinal mucositis following irinotecan administration. McLTP 1 (0.5, 2 and 8 mg/kg, i.v.) was injected into mice 1h before irinotecan administration (75 mg/kg, i.p.; 4 days), and then for additional 6 days. Seven days after the rst dose of irinotecan, diarrhea was assessed and the intestine was removed for histological evaluation, assessment of intestinal over-contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 57 publications
1
3
0
Order By: Relevance
“…Ifosfamide increased tissue MPO levels, which were significantly reduced after treatment with McLTP1 at doses of 10 and 20 mg/kg. Our findings are in line with previous studies, in which McLTP1 (8mg/kg) reduced MPO activity in the duodenum of mice subjected to intestinal mucositis by irinotecan [42]. In fact, previous research with other models of inflammation has already shown that polysaccharides from Morinda citrifolia are able to attenuate classic signs of inflammation such as edema in a model of experimental colitis induced by acetic acid [46].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Ifosfamide increased tissue MPO levels, which were significantly reduced after treatment with McLTP1 at doses of 10 and 20 mg/kg. Our findings are in line with previous studies, in which McLTP1 (8mg/kg) reduced MPO activity in the duodenum of mice subjected to intestinal mucositis by irinotecan [42]. In fact, previous research with other models of inflammation has already shown that polysaccharides from Morinda citrifolia are able to attenuate classic signs of inflammation such as edema in a model of experimental colitis induced by acetic acid [46].…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies with McLTP1 described in the literature already show its anti-inflammatory and antioxidant activity in different preclinical models of nociception, intestinal mucositis by irinotecan, antimicrobial and protective activity on sepsis, nephro and gastroprotective. Therefore, the protein was considered a potential uroprotector to be investigated [42][43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…Aiming to verify results of histologic analysis, the inflammatory profile of burn wounds and treatments with silver sulfadiazine and McLTP1 was evaluated. MPO activity, a marker of neutrophil presence, was increased after 3 days of burn, in according with other protocols 31 . Indeed, neutrophils are the more abundant cells after 48 hours of burns 43 .…”
Section: Discussionmentioning
confidence: 66%
“…McLTP1 is a lipid transfer protein isolated from Noni seeds that has been demonstrating anti-inflammatory, antinociceptive and antioxidant effects 29,30,31,32 . Recently, this protein showed an in vitro antibacterial effect in Sthaphylococcus aureus and Staphylococcus epidermidis 33 , predominant bacteria in secondary skin infections 34,35 .…”
Section: Introductionmentioning
confidence: 99%